Statistical optimisation for enhancement of phenol biodegradation by the Antarctic soil bacterium Arthrobacter sp. strain AQ5-15 using response surface methodology - Subramaniam, K.; Shaharuddin, N. A.; Tengku Mazuki, T. A.; Zulkharnain, A.; Khalil, K. A.; Convey, P.; Ahmad, S. A. (Triveni Enterprises, 2020)
Aim: Methodology: Results: Interpretation: Effective bioremediation requires optimisation of conditions under which the process takes place. In this study, an Antarctic soil bacterium, Arthrobacter sp. strain AQ5-15, was evaluated for phenol biodegradation under statistically optimised conditions. The composition of degradation media and the culture conditions for this study were determined according to the experimental requirements obtained from Plackett-Burman factorial design (PB) and Box-Wilson Central Composite Design (CCD), respectively. Phenol degradation was monitored by 4-aminoantipyrine colorimetric assay and bacterial growth was quantified by measuring optical density (OD ) at 72 hr. 600 nm A preliminary screening experiment using the Plackett-Burman design indicated that all the factors screened (ammonium sulphate concentration, sodium chloride concentration, pH and temperature) had significant influence on degradation performance. Response Surface Methodology was then utilised to further optimise the phenol-degrading process using Central Composite Design. The maximum percentage of phenol degradation achieved with CCD was 99.42%, -1 -1 under medium conditions of 0.15 g l (NH ) SO , 0.13 g l NaCl, pH 7.25 and 4 2 4 incubation at 15°C for 72 hr. The strain could degrade phenol when exposed to an -1 initial concentration of up to 1.5 g l under these optimised conditions. The tolerance and degradation characteristics of strain AQ5-15 suggest that it has potential application in bioremediation of polluted sites and in the treatment of relatively cool water bodies contaminated with phenol.